Transmission Design and Simulation Analysis of Lower Exoskeleton Rehabilitation Device - Hu Qingming; Guo Qiang; Guo Jianhua (Jixie chuandong)
The hydraulic lower exoskeleton rehabilitation device is proposed to solve the problem of patient lying on the bed can’t walk and the aged leg rehabilitation training. Two kinds of transmission schemes are put forward as its main transmission mechanism,which are crank- slider mechanism and slider- rocker mechanism. With the main construction member motion analysis of the crank- slider mechanism and slider- rocker mechanism,the main technical parameters are obtained. And the displacement,velocity and acceleration of the components are acquired and compared simultaneously. Then the slider- rocker mechanism is determined as the main transmission mechanism of the hydraulic lower exoskeleton rehabilitation device. Finally,the three dimensional assembly model of the legs rehabilitation device is established with Solid Works,and the simulation and mechanics analysis are conducted. The results show that the proposed hydraulic legs rehabilitation device can achieve the expected movement purpose and meet the requirements of rehabilitation training.